Settler colonialism, decolonization and radicalizing transitional justice - Park, Augustine S. J. (International journal of transitional justice, 2020)
Although transitional justice has been mobilized to address violence perpetrated under regimes of settler colonialism that are also established liberal democracies, this article theorizes the inability of paradigmatic transitional justice to confront settler colonialism. The liberal teleology of transitional justice risks working to realize the self-supersessionist goal of replacing the colony with a ‘post-colonial’, settler/settled polity. Drawing on Indigenous scholars, decolonization is explored through refusal, resurgence and prefiguration. The article advances a counterfactual proposition: If transitional justice is radicalized it has the potential to contribute to decolonization through decentring the state, inter-nationalizing the justice relation, challenging the legitimacy of the settler regime and abandoning liberal teleology. The article argues for a decolonizing acceptance of indeterminacy and uncertainty.